Criminal Law Reform for Wildlife Protection Based on Ecological Justice: A Normative Legal Approach in Indonesia - Benny Karya Limantara (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Indonesia's exceptional biodiversity is increasingly threatened by wildlife crime, while the legal framework established under Act No. 5 of 1990 has become inadequate for addressing contemporary ecological challenges. Although previous studies have identified weaknesses in wildlife law enforcement, few have translated ecological justice into concrete principles for reforming Indonesian wildlife criminal law. This study examines the urgency of wildlife criminal law reform and develops an ecocentric framework grounded in ecological justice. It employs normative (doctrinal) legal research, using statutory, conceptual, and comparative approaches grounded in legislation, international legal instruments, judicial decisions, scholarly literature, and institutional reports. Legal materials were analysed qualitatively through grammatical, systematic, teleological, evaluative, and prescriptive reasoning. The findings reveal that outdated legal provisions, disproportionate sanctions, fragmented institutions, and limited recognition of ecological integrity as a protected legal interest constrain the current framework. Comparative analysis highlights the importance of aggravated offences, corporate liability, confiscation and restoration orders, proportionate sanctions, and specialised wildlife crime units. The study concludes that Indonesian wildlife criminal law should adopt an ecocentric approach integrating ecological justice into offence structures, sanctions, and institutional mechanisms. This study contributes a normative framework for strengthening Indonesian criminal law reform and biodiversity protection through ecologically oriented wildlife governance.